PELATIHAN MEMBATIK UNTUK MEMUNCULKAN PRODUK UNGGULAN MASYARAKAT BULUSAN DALAM PRODUKSI PARIWISATA - Agus Mursidi; Rachmaniah Mirza Hariastuti; Harwanti Noviandari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
Banyuwangi is a district that is developing its city towards a tourist city so that the growth of industry and hospitality is very rapid but does not necessarily bring welfare impacts to the surrounding community because the absorption of its employees is not from surrounding residents other than that the natural conditions of the Bulusan Village can only be planted with corn and coconut. The problem that arises is that in Bulusan Village there are many tourist areas and hotels, but the people cannot enjoy it yet. So to answer the problem can use the road are: 1) Training, assistance; 2) Community empowerment activities in order to be able to create new community-based and environment-based jobs are carried out jointly between students and the community accompanied by experts in their fields. The method used for this program is the socialization of the team that offers skills training assistance. Followed by training material. Then followed by the practice of making batik and bambo woven. The results of this dedication are obtained three elements of an increase in human resources to increase their knowledge and appearance. Keywords: Training, Batik, Bulusan